PELATIHAN MANAJEMEN KEUANGAN BERBASIS DIGITAL UNTUK UMKM AB MART DAN AB CHICKEN - Susilawati, Susilawati; Novitasari, Kartika (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This Community Service Program aims to improve the financial management skills of AB Mart and AB Chicken SME actors through digital-based financial management training. The implementation methods include initial observation, practical training in the use of digital financial applications, intensive mentoring, and evaluation of participants' understanding. The results of the community service show a significant increase in the accuracy of financial recording, digital literacy, the ability to read automated financial reports, and a shift in decision-making patterns from intuition to a data-based approach. In addition, there has been an increase in internal transparency and accountability through real-time transaction monitoring, which strengthens coordination among business team members. Although there were obstacles in the form of low technological familiarity among some participants, the gradual mentoring approach proved effective in overcoming digital resistance. Overall, this training had an impact on transforming financial behavior and increasing the digital capacity of MSMEs, thereby contributing to strengthening business competitiveness in the digital era.